AN EFFECTIVE PLACE TO ORGANIZE FINE ART AND APPLIED ART LESSONS IN PRIMARY EDUCATION THROUGH NEW INNOVATIVE TECHNOLOGIES (American Journal of Interdisciplinary Research and Development, 2023)
This scientific article examines the effective role of organizing Fine Art and Applied Art classes within the primary education curriculum by using new innovative technologies. The introduction of technology has provided teachers with many tools to enhance the teaching and learning experience in these subjects. By considering the benefits, challenges, and strategies of technology integration, this study highlights the potential for creativity, critical thinking, and skill development in elementary students in the Visual and Applied Arts fields.